HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT GIGI DENGAN PENERAPAN KOMUNIKASI TERAPEUTIK DI BP GIGI PUSKESMAS KABUPATEN AGAM - Zulfikri Zulfikri (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe association of knowledge and dental nurse attitudes with therapeutic-communication application in dental clinic of Puskesmas Kapubaten AgamABSTRACTOne of the competence standards of dental nurses is able to conduct a therapeutic communication at the dental health service with their clients; among the communicated matters are describing the activities that will be conducted, giving the clients the chances to ask, planning the follow-ups, and conducting contracts of the next dental care. This research has the objective of analyzing the factors influencing dental nurses in implementing the therapeutic communication at the Dental Service Division of the Public Health Center of Agam Regency.This research was an explanatory research, with survey as the research method, using the cross-sectional approach. The research samples were all dental nurses working at the Public Health Center of Agam Regency, as many as 41 people. Data were collected by direct interviews using a structured questionnaire.The research results showed that the implementation of therapeutic communication at the Dental Service Division of the Public Health Center of Agam Regency was still inadequate (63.4%). Variables that were significantly related to the dependent variable is the attitude variables (p. Value 0.008), whereas knowledge of dental nurses did not reveal any significant association with the application of therapeutic communication (p. Value 0.743). Key words : therapeutic communication, competence of dental nurses, dental service division of the public health center